2020
DOI: 10.1002/ab.21913
|View full text |Cite
|
Sign up to set email alerts
|

The longitudinal relationship between angry rumination and reactive–proactive aggression and the moderation effect of consideration of future consequences‐immediate

Abstract: The idea that influential factors for two subtypes of aggression (reactive and proactive aggression) should be different is popular, but the common influential factors have not been examined. Such an examination could help understand the influential factors of aggression from the perspective of multiple motivations affecting the development of aggressive motivations over time. The present study argued that angry rumination would be a common influential factor for both reactive and proactive aggression. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 71 publications
2
17
0
1
Order By: Relevance
“…Figure 1 showed that anger rumination is a risk factor for reactive aggression. This result was consistent with the previous study finding that anger rumination can predict reactive aggression after a 6 month period ( Wang et al, 2020 ), it also supported and expanded our understanding of the multiple systems model ( Denson, 2013 ). According to the multiple systems model, anger rumination following a provocation increases impulsive aggression and decreases the likelihood of refraining from aggression, which can be due to the failure of self-control ( Denson et al, 2011 ).…”
Section: Discussionsupporting
confidence: 92%
“…Figure 1 showed that anger rumination is a risk factor for reactive aggression. This result was consistent with the previous study finding that anger rumination can predict reactive aggression after a 6 month period ( Wang et al, 2020 ), it also supported and expanded our understanding of the multiple systems model ( Denson, 2013 ). According to the multiple systems model, anger rumination following a provocation increases impulsive aggression and decreases the likelihood of refraining from aggression, which can be due to the failure of self-control ( Denson et al, 2011 ).…”
Section: Discussionsupporting
confidence: 92%
“…In contrast, measuring proactive aggression in laboratory paradigms is more complicated because the paradigm has to elicit instrumental aggression without any sort of provocation. Thus, the majority of studies on proactive aggression only used self-reported questionnaires (e.g., Euler et al, 2017 ; Zhu et al, 2019b ; Wang et al, 2020 ). To measure proactive aggression, a paradigm should capture unprovoked aggressive behaviors, which aim at obtaining a goal such as a reward (instrumental motivation).…”
Section: Introductionmentioning
confidence: 99%
“…The link can be explained by the script theory. Frequent fantasizing about how to hurt others (e.g., revenge, physical aggression, and derogation) may increase their motivation of revenge (Wang et al, 2020), which urges people pay more attention to violence events around them to search for the appropriate revenge means. Moreover, hostile automatic thoughts will increase the accessibility of the hostile or aggressive scripts via the constant rehearsal and retrieval, thereby making individuals interpret the environment as more hostile (Huesmann, 2018).…”
Section: The Longitudinal Relation Between Violence Exposure In Daily...mentioning
confidence: 99%